AB0130 SERUM ATHEROGENICITY IN WOMEN WITH UNTREATED SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Gerasimova, H.; Popkova, T.; Gerasimova, D.; Sobenin, I.; Lila, A.
Abstract : Background: Systemic lupus erythematosus (SLE) is associated with an unexplained increase cardiovascular risk. The nature of the factors that contribute to progression of atherosclerosis were identified using the method for determining the atherogenicity of blood serum in cell culture in cell culture (in vitro). The term "atherogenicity" is meant as the ability of the serum and/or its components to induce intracellular accumulation of cholesterol in cultured cells. Objectives: To compare atherogenicity of blood serum in women with untreated SLE and healthy women. Methods: Thirty seven women (median age 30[21;39] years) with active SLE (median disease duration 45[3;102] months; SLADAI 17 [8;34]) were enrolled in the study. Lupus nephritis are defined in 15 (41%), Antiphospholipid syndrome (APS) – in 8 (22%) of 37 SLE patients (pts). The control group consisted of 30 women, median age 31[25;39] years. Atherogenicity of blood serum was determined in the culture of murine macrophages. Peritoneal macrophages were isolated from the ascitic fluid of the line mice according to the generally accepted method J. Goldstein et al (1979y). Serum atherogenicity was determined by the accumulation of intracellular cholesterol induced by 10% of the blood serum of the patients, and expressed as a percentage of the content of cholesterol in the control cells. Results: Elevated atherogenicity of blood serum was detected more frequently in SLE pts (24/72 (65%) vs healthy controls (5/30 (17%), p<0, 01). The blood serum of SLE pts caused a 3-7-fold accumulation of intracellular cholesterol, which significantly differed from healthy women (203±136% vs 127±42%, p<0, 001). The ability to stimulate the accumulation of cholesterol esters in murine macrophages was not associated with age, duration of the disease, lipid spectrum and was the highest in pts with nephritis (305±141% vs 180±52%, p<0, 05) and APS (253±130% vs 119±75%, p<0, 05). Conclusion: Serums of women with untreated SLE may stimulate the accumulation of cholesterol in mouse macrophages unlike of healthy women. The highest atherogenicity was found in blood serum of SLE pts with nephritis and APS. Disclosure of Interests: None declared